Crystal preferred orientations, deformation mechanisms and seismic properties of high pressure metamorphic rocks from the Central Qiangtang metamorphic belt, Tibetan Plateau. (April 2021) - Cao, Yi; Du, Jinxue; Jung, Haemyeong; Jung, Sejin; Lee, Jaeseok; Park, Munjae; Kim, Junha
Abstract: Crystal preferred orientation (CPO) of high pressure metamorphic rocks is an important contributor to seismic anisotropy in the subduction interface and continental crust. However, the mechanisms of deformation and CPO development, as well as the effect of CPO patterns on the seismic anisotropies remain not fully solved. By analyzing the microstructures, CPOs and seismic properties of the high pressure rocks from the Central Qiangtang metamorphic belt in the northern Tibetan Plateau, we found that the mineral CPOs (e.g., omphacite and amphibole) are developed dominantly by non-dislocation based deformation mechanisms in the eclogites and amphibolites, while quartz and phengite CPOs are primarily formed by dislocation creep in the garnet-quartz-mica schists. The variations of CPO patterns are mainly controlled by the strain geometry and/or strain magnitude, which also regulate the first-order symmetry patterns of seismic anisotropies among samples. Besides, amphibole enrichment can remarkably increase the anisotropies and decrease the velocities of seismic waves in the eclogite‒amphibolite suite. A combination of seismic parameters such as Vp, Vs, Vp/Vs ratio, intensities and symmetries of P-wave anisotropy (AVp) and shear wave splitting (AVs), and P- or S-wave reflection coefficients can be used to discriminate eclogites, amphibolites and their garnet-quartz-mica schists country rocks at depth when high resolution seismic methods can be applied. Notably, amphibolite and garnet-quartz-mica schists showing moderate-to-large AVp and max. AVs can make considerable contributions to field-observed crustal anisotropy near the strike-slip continental shear zones or mantle wedge anisotropy in the subduction zones. Highlights: Deformation mechanisms differ between eclogite, amphibolite and felsic schist. Symmetries of CPO and seismic anisotropy are mainly controlled by strain geometry. Amphibole affects seismic velocity and anisotropy in eclogite‒amphibolite notably. Seismic parameters can be combined to differentiate metamorphic rocks at depth. Modest-to-large seismic anisotropy can be made by amphibolite and felsic schist.